Day 4 Thu, November 03, 2022 2022
DOI: 10.2118/211465-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing CO2 Foam Viscosity and Stability at Harsh Reservoir Conditions Through the Synergetic Interactions of Surfactant and Polymer

Abstract: The injection of foam into petroleum reservoirs has attracted special interest in the last decades. Some applications include; fracturing, stimulation, and gas mobility control during gas EOR processes. Utilizing foam in well stimulation is promising as it consumes less water than water-based fracturing fluid, is less damaging to the formation, and provides an effective proppant carrying capacity and transportation. This paper studies the synergic effects of surfactant-polymer system on the rheology and stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The performance of foam viscosity is strongly related to the bubble size, bubble density, and bubble shapes and its response to the deformation in the dynamic state . Additionally, the experimental studies showed that foam viscosity varied with many parameters, including foam quality, pressure, temperature, shear rate, salinity, and additives. …”
Section: Introductionmentioning
confidence: 99%
“…The performance of foam viscosity is strongly related to the bubble size, bubble density, and bubble shapes and its response to the deformation in the dynamic state . Additionally, the experimental studies showed that foam viscosity varied with many parameters, including foam quality, pressure, temperature, shear rate, salinity, and additives. …”
Section: Introductionmentioning
confidence: 99%